Is the total number of blood transfusion in β-thalassemia major patients can be used to assess their serum ferritin levels ? (Tikrit Journal of Pharmaceutical Sciences, 2023)
β-thalassemia is an inherited blood disorder in hemoglobin synthesis that results in anemia, growth retardation and certain pathological changes. The treatment of choice for β-thalassemia is the repeated blood transfusion, but unfortunately it results in an iron overload with additional risk factors. The present study aims to evaluate iron profile in transfusion dependent β-thalassemia patients and the effects of repeated blood transfusion on serum ferritin level and the possibility of using the total number of blood transfusion to predict serum ferritin level. 40 transfusion dependent β-thalassemia patients were included in the present study all dependent on blood transfusion only with age range 1-4 years old. A control group of 20 apparently healthy children with age range 1-4 years old was used for comparison. Blood sample of 5 ml was collected from each individual and tested for serum levels of iron, TIBC, % saturation, and serum ferritin. The present study revealed significant changes in the levels of iron profile parameters between patients and control subjects manifested by significantly elevated serum iron and ferritin levels with significantly decreased serum TIBC. Iron status and iron overload in transfusion dependent β-thalassemia patients revealed a significant correlation between serum ferritin level and the number of transfused RBCs units. However this correlation is a rough correlation and some times unpredictable and it could not be used to assess the level of serum ferritin as used by some physicians.